Control interno de la gestión administrativa y financiera de la Empresa Balitsa S.A. del cantón urdaneta en el período 2020 – 2021. - Quintero Muñoz, Melina Dexire (2022)
In this case study, the lack of internal control of the company BALITSA S.A. was analyzed, and its negative effect on the profitability of the year 2021 and for its comparison in the year 2020. The private company is dedicated to purchasing activities of wood, production, cultivation, sale and other activities with wood in general. This project focuses on the administrative and financial areas, since they are very important pillars within any organization, which is why it is essential to know about the internal control that must be carried out. For this, goals were established that allowed the main objective of this study to be achieved, based on the analysis of the processes for a correct internal control of the activities and operations in the administrative and financial area, which reduce the risk factors that affect profitability. of the BALITSA company. In the methodology, qualitative, quantitative, statistical methods were used, and the execution of an interview addressed to the manager and owner of the company, in a way that allowed obtaining direct and reliable information about the controls that are carried out within the entity, as well as as well as allowed to analyze the weaknesses. In the results, the information obtained is presented and the effects of the problem and the consequences reflected in the profitability of BALITSA S.A. are discussed. Conclusions and recommendations were established, which were developed from the observation and critical analysis of the administrative and financial area, so that they were developed with the purpose that the company avoid future risks and have better opportunities in decision making. Finally, the respective annexes referring to the research carried out are exposed.